Incorporating shared measurement in social change initiatives: benefits, challenges, and lessons learned. (19th April 2021) - Judelsohn, Alexandra; Hoey, Lesli; Shapiro, Lilly Fink; Colasanti, Kathryn
Abstract: Collective impact is increasingly being adopted as a systems-based approach for addressing complex social problems. Yet one of the critical components, shared measurement, remains challenging to implement (Hanleybrown, Kania and Kramer, 2012 ). Based around a common set of metrics, shared measurement is foundational to offering multi-organizational initiatives ongoing feedback that can allow them to share the lessons learned, make adjustments, and document the outcomes of their joint efforts. This paper examines the lessons practitioners have learned as they applied shared measurement strategies across diverse initiatives. We scrutinized food systems initiatives, in particular, hypothesizing that the complex, adaptive nature of food systems makes it more challenging to apply a commonly agreed upon set of measures in comparison to other sectors. Through seventeen semi-structured interviews, we found that interviewees shared similar perceptions about the multiple benefits of shared measurement whether they worked in food systems or other fields. Based on the major challenges they encountered, three primary lessons emerged about what it takes to establish a successful shared measurement system: trust across collaborating organizations, a streamlined process, and sufficient funding.